Ablasio Retina: Etiologi, Faktor Resiko, Diagnosis, dan Tatalaksana - Salsabila Haqya Kusuma; Rani Himayani; Putu Ristyaning Ayu Sangging (CV. Jasa Sukses Abadi, 2023)
The separation of the neurosensory layer on the retina with the pigment epithelium layer at the bottom is an eye disease called Retinal Detachment. Retinal detachment occurs when the EPR and neurosensory layers are no longer attached to each other. Based on previous research, it was found that in the Iowa area conducted by Haimann et al., as well as research conducted in Minnesota by Wilkes et al., there were 12 cases of retinal detachment per 100,000 people each year. This research was conducted with the type of literature review research which has the aim of collecting data that is relevant to the material that is interested in being studied at this time, namely regarding Retinal Detachment or Retinal Detachment. The inclusion criteria used by the researchers were a literature that was uploaded or published at the latest in 2012. The exclusion criteria used were literature published in 2011 and below (examples: 2011, 2010). The results of the research that has been done are in the form of in-depth material regarding retinal detachment. Based on the theory introduced by the American Optometric Association (AAO), retinal detachment is categorized into rhegmatogenous which most often causes emergency conditions, and non-rhegmatogenous. Risk factors that affect retinal detachment are myopia, age, gender, trauma, the presence of peripheral retinal degeneration, and others. Meanwhile, the recommended treatment or therapy is vitrectomy surgery, scleral buckle, pneumatic retinopexy, and laser photocoagulation. Because retinal detachment can be an emergency case, doctors need to be aware of the signs and symptoms that lead to this disorder.